Prediction of pedestrian trajectory with a moving camera using deep learning - Xiong, Xincheng (Nanyang Technological University, 2020)
Predicting the motion of pedestrian have wide range of applications like social-behavior understanding, autonomous system, modelling crowds motion and so on. In case of autonomous systems, like mobile robot, obtaining the foreseeable position of pedestrian allows the robot to make fast and safe decisions, like stopping before hitting the pedestrian feet. Making such decision require knowledge of robot's position and that of pedestrians moving around it in an accurate manner. As the robot and pedestrian both can be dynamic, the problem of predicting the pedestrian position from moving robot become a more challenging task.